2020
DOI: 10.3126/mjpahs.v3i1.31924
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients with Stroke in Western Region of Nepal: A Hospital based Retrospective Study

Abstract: Background: Stroke is one of the most common cause of morbidity and mortality worldwide. Approximately 50-85 percent of strokes are due to ischemic cerebral infarction and 7-27 percent to intracerebral hemorrhage. Since the incidence of stroke is increasing in our country, the study aims to identify various factors associated with stroke. Materials and Methods: This is a retrospective study of 86 patients admitted in A & B International Hospital, which is a private hospital located in Pokhara ,Nepal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The sample size of quantitative studies ranged from nine to 1017 participants. Studies were mainly published in national journals (n = 48) [ 10 – 21 , 23 – 35 , 37 , 39 , 41 – 43 , 45 – 56 , 58 60 , 63 , 64 ], and only seven studies were published in international journals [ 22 , 36 , 40 , 44 , 57 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size of quantitative studies ranged from nine to 1017 participants. Studies were mainly published in national journals (n = 48) [ 10 – 21 , 23 – 35 , 37 , 39 , 41 – 43 , 45 – 56 , 58 60 , 63 , 64 ], and only seven studies were published in international journals [ 22 , 36 , 40 , 44 , 57 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The details of the outcome parameters are presented in Table 2 under the main focus area. Fifty studies reported on the types of strokes [ 10 62 , 64 ], and 44 studies investigated risk factors in stroke patients [ 10 , 12 – 14 , 16 , 18 26 , 28 , 30 – 33 , 35 – 37 , 39 – 41 , 43 45 , 47 – 54 , 56 – 59 , 61 – 64 ]. Six studies described using CT scan [ 10 , 11 , 18 , 28 , 47 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations